THE IMPORTANCE OF CULTURAL IMMERSION IN LANGUAGE LEARNING (Scientific Conference on Multidisciplinary Studies, 2025)
The role of cultural absorption in the process of language learning is incomparable. The language is studied not only by a set of words and grammatical rules, but also by it the worldview, values, customs and historical experiences of a particular people. Culture as an integral part of language allows language learners to gain a deeper understanding of language, applying it naturally and effectively. Therefore, the process of cultural absorption in language learning requires a broader and more meaningful approach to language than just technical learning.